A kind of low heat high grade cement and preparation method thereof
By adding yellow phosphorus slag, granulated blast furnace slag and polyacrylic/polytetrafluoroethylene admixture to low-heat high-grade cement clinker, the contradiction between early strength and low hydration heat is solved, and the synergistic effect of early strength improvement and hydration heat reduction is achieved.
Patent Information
- Application Number
- CN202310421221.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-19
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-19
AI Technical Summary
There are contradictions in the early strength and hydration heat of existing low-thermal silicate cements, and it is difficult to achieve the synergistic effect of early strength and low-hydration heat of both.
By adding yellow phosphorus slag, low-hydration heat granulated blast furnace slag and admixtures containing polyacrylic acid and polytetrafluoroethylene to low-heat high-grade cement clinker, the liquid phase formation temperature and hydration reaction rate are adjusted, the heat of hydration is reduced and early strength is improved.
The early strength improvement and hydration heat reduction of low-heat high-grade cement was achieved. The strength was greater than 20.0MPa in 3 days, the strength was greater than 33.0MPa in 7 days, the strength was greater than 52.5MPa in 28 days, and the heat of hydration was less than 260KJ/Kg, meeting the low-heat silicate cement requirements of GB/T200-2017.
Smart Images

Figure BDA0004186866910000041 
Figure BDA0004186866910000051 
Figure BDA0004186866910000052
Abstract
Description
Technical Field
[0001] The invention relates to the field of cement and its manufacturing, and in particular to low-heat high-grade cement and a preparation method thereof. Background Art
[0002] Low-heat Portland cement is a kind of commonly used dam cement, referred to as low-heat cement. It is a hydraulic cementitious material with low hydration heat made by adding appropriate amount of gypsum to Portland cement clinker with appropriate ingredients and grinding it. Low-heat cement has low hydration heat, excellent sulfate resistance, low shrinkage and good wear resistance. Low-heat cement is particularly suitable for hydraulic mass concrete and high-strength and high-performance concrete. It has been applied to the pavement of the Capital Airport, Chengle Expressway, Beijing Fifth Ring Road Bridge and concrete products, and has achieved good results. In the development and application research, a large number of concrete tests were carried out using raw materials such as coarse and fine aggregates and fly ash used in the Three Gorges Project. At present, low-heat cement can be divided into 42.5 and 32.5 grades according to its 28-day compressive strength. The 7-day compressive strength of these two grades of low-heat cement is required to reach 13.0 and 10.0 grades respectively. The early strength is much lower than the zero-general-purpose Portland cement of the same period. It is difficult to produce high-grade cement in 28 days. At the same time, low heat cement has strict requirements on clinker. The minerals of low heat cement clinker are mainly tricalcium silicate, dicalcium silicate and tricalcium aluminate. These components are the source of early cement strength, but they will greatly increase the hydration rate and accumulated hydration heat of early cement, affecting the crack resistance and corrosion resistance of later products. Therefore, it is difficult to produce a cement with both low heat and early strength properties.
[0003] In the prior art, a large number of scholars have optimized and matched the mineral composition of silicate cement clinker to achieve the best comprehensive performance of cement, but they have never been able to break through the contradiction between low hydration heat and early strength. How to reduce the early and cumulative hydration heat of silicate cement clinker itself while improving early mechanical properties or long-term service performance, and achieve synergy between early strength and low hydration heat has become a major technical problem that the cement industry urgently needs to solve. For example, Chinese patent CN102898050B provides a high-magnesium micro-expansion low-heat cement, which only reduces cracks caused by low hydration heat by utilizing the delayed expansion of magnesium oxide. The 28-day compressive strength of the high-magnesium micro-expansion low-heat cement does not reach 52.5MPa. Summary of the invention
[0004] In view of the deficiencies of the above prior art, the present invention provides a low-heat and high-grade cement, which has both low-heat and high-grade properties, with a 3-day strength greater than 20.0MPa, a 7-day strength greater than 33.0MPa, and a 28-day strength greater than 52.5MPa; a 3-day hydration heat less than 215KJ / Kg, and a 7-day hydration heat less than 260KJ / Kg, meeting the requirements for low-heat silicate cement in GB / T200-2017, and is specifically achieved through the following technologies.
[0005] The invention provides a low-heat high-grade cement, which is obtained by mixing low-heat high-grade cement clinker with gypsum, an admixture and granulated blast furnace slag; the raw material ratio of the low-heat high-grade cement clinker is as follows: 75-86wt% of lime, 3-6wt% of tailings waste, 10-16wt% of clastic rock and 1-3wt% of yellow phosphorus slag; the admixture is polyacrylic acid and polytetrafluoroethylene, and the mass ratio of polyacrylic acid to polytetrafluoroethylene is 1-2:1.
[0006] Preferably, the raw material ratio of the above-mentioned low-heat high-grade cement clinker is as follows by weight percentage: 83wt% of lime, 4.5wt% of tailings waste, 11wt% of clastic rock, and 1.5wt% of yellow phosphorus slag.
[0007] Furthermore, the fluoride ion content of the yellow phosphorus slag is greater than or equal to 2.0%.
[0008] Furthermore, the mineral composition of the above-mentioned low-heat high-grade cement clinker is as follows in terms of mass percentage: tricalcium aluminate is less than or equal to 7%, dicalcium silicate is greater than or equal to 33%, free calcium oxide is 0.5-1%, and magnesium oxide is 1.5-3.5%.
[0009] Furthermore, the alkali content of the low-heat high-grade cement clinker is 0.3-0.55%.
[0010] The calcareous material is one or more of limestone, marl, shell, calcareous ginger stone, and calcareous river pebbles; the tailings waste is iron tailings; and the clastic rock is at least one of shale and sandstone.
[0011] The surface area of the above-mentioned granulated blast furnace slag after grinding needs to be controlled at 370-400m 2 / kg.
[0012] The role and principle of the above raw material components in the process of preparing low-heat high-grade cement are as follows: the yellow phosphorus slag component in the raw material ingredients is conducive to reducing the formation temperature of the liquid phase and increasing the amount of the liquid phase, thereby promoting the formation of the silicate clinker phase and improving the strength of the low-heat high-grade cement clinker. Adding low-hydration heat granulated blast furnace slag to the clinker reduces the hydration heat of the cement and ensures the early strength of the cement. Adding an admixture containing polyacrylic acid and polytetrafluoroethylene to the clinker, the carboxyl group of polyacrylic acid will enrich calcium ions on the polymer surface through complexation, thereby enriching silicate ions around the polymer. This process reduces the CSH nucleation rate and inhibits the cement hydration heat process. At the same time, polytetrafluoroethylene has excellent electronic insulation, which can reduce the complexation reaction of calcium ions and water molecules, so that as many calcium ions as possible are complexed with carboxyl groups, making the hydration heat inhibition effect of polyacrylic acid better. When granulated blast furnace slag is used together with yellow phosphorus slag and admixtures, the three have a synergistic effect: the admixture and yellow phosphorus slag promote the compressive strength enhancement function of granulated blast furnace slag, and at the same time, the inhibitory effect of the admixture on hydration heat is also enhanced. The three together break through the contradiction between hydration heat and early strength of cement, and achieve the synergistic effect of cement early strength and low hydration heat.
[0013] The present invention also provides a method for preparing low-heat high-grade cement, which is characterized by comprising the following steps:
[0014] S1, mixing the raw materials of the low-heat high-grade cement clinker, crushing, grinding and sieving to obtain a mixture;
[0015] S2, calcining the mixture in S1 at 1350-1450°C for 40-50min, and rapidly cooling to below 150°C to obtain low-heat high-grade cement clinker;
[0016] S3, mix and grind the medium-low heat high-grade cement clinker in S2 with gypsum and admixtures, and control the specific gravity at 290-320m 2 / kg;
[0017] S4. Grind the granulated blast furnace slag separately, and control its specific gravity at 370-400m 2 / kg;
[0018] S5. Stir and mix the products obtained in step S3 and step S4 to obtain low-heat high-grade cement.
[0019] The mass percentages of the components in the low-heat high-grade cement are: 30-40wt% of granulated blast furnace slag, 0.2-0.3wt% of admixture, 55-65wt% of low-heat high-grade clinker, and 5wt% of gypsum.
[0020] Compared with the prior art, the present invention is beneficial in that:
[0021] 1. The raw material formula provided by the present invention contains yellow phosphorus slag, which is beneficial to reduce the formation temperature of the liquid phase, increase the amount of the liquid phase, and thus promote the formation of the silicate clinker phase and improve the strength of the low-heat high-grade cement clinker. By adding low-hydration heat granulated blast furnace slag to the low-heat high-grade cement clinker, the cement hydration heat is reduced while ensuring the early strength of the cement. The low-heat high-grade cement provided by the present invention has a 3-day strength greater than 20.0MPa, a 7-day strength greater than 33.0MPa, and a 28-day strength greater than 52.5MPa, and the cost of the admixture is low, which reduces the overall cost of preparing cement.
[0022] 2. The present invention also adds an admixture containing polyacrylic acid and polytetrafluoroethylene to the low-heat high-grade cement clinker. The carboxyl group of polyacrylic acid can enrich calcium ions on the polymer surface through complexation, thereby enriching silicate around the polymer, reducing the CSH nucleation rate and inhibiting the cement hydration heat process. At the same time, polytetrafluoroethylene can reduce the complexation reaction of calcium ions and water molecules, so as to make more calcium ions complex with carboxyl groups as much as possible, so that the hydration heat inhibition effect of polyacrylic acid is better, so that the hydration heat of the prepared cement is less than 215KJ / Kg in 3 days and less than 260KJ / Kg in 7 days.
[0023] 3. The above-mentioned yellow phosphorus slag, admixtures and granulated blast furnace slag are used simultaneously, so that the compressive strength and hydration heat performance of the prepared cement are better than the effect of using any one of the components alone, thereby maximizing the functions of each component and achieving the synergistic effect of early strength and low hydration heat of cement. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] The main chemical compositions of the raw materials used in the specific implementation of the present invention are shown in Table 1 below:
[0026] Table 1 Main chemical composition of raw materials (wt%)
[0027] raw material <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO limestone 6.82 1.07 0.42 48.84 1.00 Iron tailings 37.16 4.11 29.41 15.06 1.44 Steel slag 20.58 6.76 19.56 31.81 8.95 shale 72.71 10.84 7.42 1.19 0.63 Granulated blast furnace slag 33.57 16.91 1.27 39.28 6.92 Yellow phosphorus slag 40.06 4.96 0.59 42.28 2.42
[0028] Unless otherwise specified in the following examples and comparative examples, the method for preparing cement comprises the following steps:
[0029] S1, mixing the components of the raw material, crushing, grinding and then sieving to obtain a mixture;
[0030] S2, calcining the mixture in S1 at 1400°C for 50 minutes, and rapidly cooling to below 150°C to obtain low-heat high-grade cement clinker;
[0031] S3, mix and grind the medium-low heat high-grade cement clinker in S2 with gypsum and admixtures, and control the specific gravity at 290-320m 2 / kg;
[0032] S4. Grind the granulated blast furnace slag or fly ash separately, and control its specific gravity at 370-400m 2 / kg;
[0033] S5. Stir and mix the products obtained in step S3 and step S4 to obtain low-heat high-grade cement.
[0034] The compositions of low-heat high-grade cement raw materials of Examples 1-3 and Comparative Examples 1-4 of the present invention are shown in Table 2 below:
[0035] Table 2 Composition and mass percentage (wt%) of low-heat high-grade cement raw materials
[0036] In the above embodiments, the lime, iron tailings, clastic rock, and yellow phosphorus slag are ground to 200 mesh and then mixed uniformly to obtain low-heat high-grade cement raw material, and the low-heat high-grade cement raw material is calcined at a high temperature of 1350-1450° C. in a new cement dry kiln system for 50 minutes, and cooled to below 150° C. to obtain low-heat high-grade cement clinker, and the mineral composition of the low-heat high-grade cement clinker is measured, as shown in Table 3 below:
[0037] Table 3 Mineral composition of low-heat high-grade cement clinker
[0038] Tricalcium aluminate Dicalcium Silicate Free calcium oxide Magnesium Oxide Example 1 4.4 41.0 0.75 1.70 Example 2 4.3 34.6 0.69 1.73 Example 3 4.2 34.1 0.95 1.67 Comparative Example 1 4.1 33.9 0.88 1.67 Comparative Examples 2-4 4.4 41.0 0.63 1.70
[0039] The low-heat high-grade cement clinker obtained in each embodiment and comparative example is mixed with gypsum, admixture, granulated blast furnace slag or fly ash to obtain low-heat high-grade cement. The mass percentages of low-heat high-grade cement clinker, gypsum, admixture, and granulated blast furnace slag in each embodiment and comparative example are shown in Table 4 below:
[0040] Table 4 Composition of low-heat high-grade cement in Examples and Comparative Examples
[0041] Among the above components, the specific gravity of low-heat high-grade cement clinker, gypsum and admixture (the degree of polymerization of polyacrylic acid in the admixture is 2700-4000) after mixing and grinding is controlled at 290-320m 2 / kg, the specific surface area of granulated blast furnace slag and fly ash should be controlled at 370-400m 2 / kg. The physical properties of the low-heat high-grade cement prepared in Examples 1-3 and Comparative Examples 1-4 were tested, and the results are shown in Table 5 below:
[0042] Table 5 Physical property test results of low heat high grade cement
[0043]
[0044] Combined with the physical property data in Table 5, the analysis is carried out: By comparing Examples 1-3 of the present invention with ordinary low-heat silicate cement, it can be seen that the compressive strength of Examples 1-3 at 3 days, 7 days, and 28 days is higher than that of ordinary low-heat silicate cement, and the heat released by the hydration reaction at 3 days and 7 days is less than that of ordinary low-heat silicate cement, indicating that under the raw materials and proportions of each embodiment of the present invention, the strengthening effect of yellow phosphorus slag and granulated blast furnace slag on the early strength of cement is more obvious, and the inhibitory effect of admixture on hydration heat is also strengthened. The three together break through the contradiction between hydration heat and early strength of cement, and achieve the synergistic effect of early strength and low hydration heat. Comparing the test results of Example 1 and Comparative Example 1, the compressive strength of the low-heat high-grade cement in Comparative Example 1 is greatly reduced compared with that in Example 1, indicating that the use of fluorite to replace yellow phosphorus slag in Comparative Example 1 affects the early strength of cement, and the influence of granulated blast furnace slag on cement strength is also weakened. Comparing the test results of Example 1 and Example 2, the hydration heat of the low-heat high-grade cement in Example 2 at 3 days and 7 days is significantly higher than that of the low-heat high-grade cement in Example 1, and the compressive strength is slightly lower than that of Example 1, indicating that the use of starch in Example 2 to replace the polyacrylic acid in Example 1 not only has no obvious inhibitory effect on the early low water heat of cement, but also affects the strengthening effect of yellow phosphorus slag and granulated blast furnace slag on the early strength of cement. Comparing the test results of Example 1 and Example 3, it can be seen that the data of the hydration heat in Example 3 is significantly higher than that in Example 1, indicating that not using polytetrafluoroethylene to control the complexation of calcium ions and water molecules will affect the inhibitory effect of polyacrylic acid on hydration heat. Comparing the test results of Example 1 and Example 4, it can be seen that the performance data of the compressive strength and hydration heat of Example 4 are not as good as those of Example 1, indicating that the use of fly ash in Example 4 to replace the granulated blast furnace slag in Example 1 not only has no strengthening effect on the early strength of the cement, but also affects the hydration heat inhibition function of polyacrylic acid.
[0045] From the above analysis, it can be seen that the present invention significantly improves the efficiency of suppressing hydration heat by adding polytetrafluoroethylene to polyacrylic acid, and the simultaneous use of yellow phosphorus slag and granulated blast furnace slag can break the contradiction between hydration heat and early strength of cement, and achieve the synergistic effect of early strength and low hydration heat.
[0046] The above specific embodiments describe the implementation of the present invention in detail, but the present invention is not limited to the specific details in the above embodiments. Within the scope of the claims and technical concept of the present invention, the technical solution of the present invention can be modified and changed in many simple ways, and these simple modifications all belong to the protection scope of the present invention.
Claims
1. A low-heat high-grade cement, characterized in that: The low-heat high-grade cement clinker is prepared by mixing gypsum, admixture and granulated blast furnace slag. The mass percentage of each component in the low-heat high-grade cement is: 30-40wt% granulated blast furnace slag, 0.2-0.3wt% admixture, 55-65wt% low-heat high-grade clinker and 5wt% gypsum; the raw material ratio of the low-heat high-grade cement clinker is: 75-86wt% lime, 3-6wt% tailings waste slag, 10-16wt% clastic rock and 1-3wt% yellow phosphorus slag; The additive is a mixture of polyacrylic acid and polytetrafluoroethylene; The mass ratio of the polyacrylic acid to the polytetrafluoroethylene is 1-2:1; The tailings waste is iron tailings.
2. The low-heat high-grade cement according to claim 1, characterized in that: The raw material proportion of the low-heat high-grade cement clinker is as follows by weight percentage: 83 wt% of lime, 4.5 wt% of tailings waste, 11 wt% of clastic rock, and 1.5 wt% of yellow phosphorus slag.
3. The low-heat high-grade cement according to claim 1, characterized in that: The mineral composition of the low-heat high-grade cement clinker is as follows in terms of mass percentage: tricalcium aluminate is less than or equal to 7%, dicalcium silicate is greater than or equal to 33%, free calcium oxide is 0.5-1%, and magnesium oxide is 1.5-3.5%.
4. The low-heat high-grade cement according to claim 1, characterized in that: The calcareous material is at least one of limestone, marl, shell, calcareous ginger stone and calcareous river pebbles.
5. The low-heat high-grade cement according to claim 1, characterized in that: The clastic rock is at least one of shale and sandstone.
6. A method for preparing low-heat high-grade cement, characterized in that: include: S1. Mixing the raw material of the low-heat high-grade cement clinker according to any one of claims 1 to 2, crushing, grinding and then sieving to obtain a mixture; S2, calcining the mixture in step S1 at high temperature, and rapidly cooling after calcination to obtain low-heat high-grade cement clinker; S3, the low-heat high-grade cement clinker in step S2 is mixed with gypsum and admixtures and ground to control the specific surface area to 290-320m 2 / kg; S4. Grind the granulated blast furnace slag separately, and control its specific gravity at 370-400m 2 / kg; S5. Stir and mix the products obtained in step S3 and step S4 to obtain low-heat high-grade cement.
7. The method for preparing low-heat high-grade cement according to claim 6, characterized in that: In steps S3 and S4, the addition amounts of the low-heat high-grade cement clinker, gypsum, admixture, and granulated blast furnace slag are 55-65wt%, 5wt%, 0.2-0.3wt%, and 30-40wt%, respectively.
Citation Information
Patent Citations
A high-magnesium micro-expansion low-heat cement and its preparation method
CN102898050B
Low heat Portland slag cement and production method thereof
CN103864320A